Multimodal dialogue on social media. Issue 5 (20th October 2018) - Jovanovic, Danica; Van Leeuwen, Theo
ABSTRACT: This paper examines digitally mediated multimodal dialogue on social media in relation to intersections between semiotic technology and social communication. In the paper, the theoretical and methodological approach to multimodal social media dialogue explores the interdependence between the design and the use of social media, showing how social media provide pre-designed templates for exchanging of information and how users respond to these technological affordances through dialogic forms. A social semiotic, multimodal approach to dialogue recognizes that dialogue involves not only a functional exchange structure, but also emotive or evaluative correspondence. This paper therefore explores social media: (i) As a functional structure, drawing on theories of exchange structure and genre, and (ii) As realizing evaluative (emotive) correspondence. Based on a corpus of social media dialogues on a number of different platforms (Instagram, Facebook, Viber, Flickr, Snapchat, WhatsApp, Twitter), the paper presents some analysis of the exchange structure and genre in social media dialogues and later emotive online correspondence in relation to "off the shelf" responses and emoticons.